Waiting for spring. 6 - Anashin, 1992- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"In her efforts to become a more proactive person, Mitsuki has agreed to join the school festival committee. Now she must lead class in putting together a café for the day of the big event. Towa has agreed to help her, but his mind is elsewhere. His team is about to have a joint practice with Hōjō, and he and Aya will finally have a basketball showdown.." -- Page [4] of cover.